Spring Water Sources Assessment and Forest Area Dynamics in Roshi and Melamchi Watersheds - Chaudhary, Santosh; Kafle, Kumud Raj; Baniya, Govinda; Shrestha, Suman; Giri, Rajiv; Shrestha, Bim Prasad; Sigdel, Ekraj (Nepal Journal of Science and Technology, 2021)
Spring-water sources mapping was carried out in eight wards of Dhulikhel and four wards of Melamchi Municipality and forest area dynamics in Roshi and Melamchi Watersheds. Ward number 9 and 10 of Dhulikhel Municipality were rich in water sources. Whereas ward number 6 of Melamchi Municipality has a good amount of water sources compared to other wards. The major spring types were depression, fractured, and contact in both the Municipalities.The percentage of forest areas in the Roshi and Melamchi watersheds seems to be fluctuating with the data compared in 2010 and 2020. There is an increase in forest areas in both municipalities in 2020. Also, the perennial spring sourceswith good discharge are prominent in having a good forest area and large watershed recharge area.